Teori Graf: Peta Cerdas untuk Era Society 5.0 - Abdurahman Hamid (Journal of Mathematics, Statistics and Applications, 2025)
The Society 5.0 era is characterized by the integration of advanced technologies such as Artificial Intelligence (AI), the Internet of Things (IoT), and big data, which collectively bring transformative changes to various aspects of human life. In this context, graph theory, as a branch of mathematics that studies network structures and relationships among elements, plays a crucial role in analyzing and optimizing complex systems. This article explores the application of graph theory across multiple domains, including social network analysis, transportation optimization, blockchain development, cybersecurity, and recommendation systems. Employing a Systematic Literature Review (SLR) approach, this study identifies the significant contributions of graph theory in developing innovative solutions that promote sustainability and enhance societal well-being. The findings reveal that graph theory serves as an essential tool in fostering the development of an intelligent, efficient, and human-centered society in the Society 5.0 era.